Adoption and Use of Social Media for Engagement by Public Relations Professionals in Broadcasting Organisations in Plateau State, Nigeria (London Journal of Research In Humanities and Social Sciences, 2024)
The innovation of the Internet facility, no doubt has significantly transformed the manner in which individuals, organisations and groups collect, create and share messages. Social media as one of the Internet-related platforms has become important in the practice of public relations. Therefore, the crux of this study is to assess the adoption and use of social media for engagement by public relations professionals in broadcasting organisations in Plateau State, Nigeria. The study collected data from 58 respondents through the employment of the quantitative research design. Technological determinism theory is used to explain the thrust of the study. The research found among others that social media has great influence in the practice of public relations in the broadcasting organisations studied. The study recommends among others that public relations professionals in media organisations should continue to take advantage of social media for better engagement with their clients.
Keywords: COVID-19 pandemic; insolvency; wage claims.; Multilingual learners; Teacher coaching; Professional development; Sheltered English instruction; Immigrant education; Social media; adoption; public relations; engagements; broadcasting.